2004
DOI: 10.1021/ma048510r
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electronic Structure of Conjugated Polymers with Fluoroalkyl Substitution:  Alternating Alkyl/Perfluoroalkyl-Substituted Polythiophene

Abstract: The electronic properties of the conjugated backbone of polythiophene can be tailored by the incorporation of alkyl and perfluoroalkyl substituents. A regioregular copolymer with alternating alkyl and perfluoroalkyl substituents displays absorption and emission maxima between those of the homopolymers composed of the individual structural units. However, the combination of the alternating electron-rich and electron-poor units, together with a small twisting influence of the perfluoroalkyl groups, provides a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
2
34
0
1
Order By: Relevance
“…For example, long perfluorinated chains directly linked to oligo- [18] and polythiophenes [19] have a strong influence on molecular packing and the absorption and emission spectra, [20] enable solubility [21] in supercritical CO 2 , and afford n-dopable semiconductors. [22] Among conducting materials, semifluorinated tetrathiafulvalene (TTF) derivatives have been prepared for Langmuir-Blodgett film formation, [23] while incorporation of highly fluorinated anions such as (CF 3 ) 3 CF(CH 2 ) 2 -SO 3 À in TTF salts also stabilized the formation of layered materials.…”
Section: Introductionmentioning
confidence: 99%
“…For example, long perfluorinated chains directly linked to oligo- [18] and polythiophenes [19] have a strong influence on molecular packing and the absorption and emission spectra, [20] enable solubility [21] in supercritical CO 2 , and afford n-dopable semiconductors. [22] Among conducting materials, semifluorinated tetrathiafulvalene (TTF) derivatives have been prepared for Langmuir-Blodgett film formation, [23] while incorporation of highly fluorinated anions such as (CF 3 ) 3 CF(CH 2 ) 2 -SO 3 À in TTF salts also stabilized the formation of layered materials.…”
Section: Introductionmentioning
confidence: 99%
“…Upon excitation, the backbone adopts a more planar conformation than that in the ground state, which increases the effective conjugation length relative to the ground state. [33,34] Absorption and emission spectra for all polymers in thin films displayed similar features to those in solution (Figure 2). Most of the compounds (P1-P4) experienced a slight bathochromic shift (2-8 nm) in absorbance as well as in PL due to solid-state effects.…”
Section: Absorption and Fluorescence Studiesmentioning
confidence: 73%
“…[5,6,13] It has been reported that bromine-metal exchange exclusively takes place at the 5-position of the bithiophene ring, leading to the formation of regioregular P3HTs, [20] owing to steric and electronic effects. P3DDFT showed poor solubility in organic solvents at room temperature, but fairly soluble in chlorobenzene at 100 8C or higher.…”
Section: Synthesis Of Bithiophene Monomermentioning
confidence: 99%
“…[7,8] Fourth, large dipole moments induced by polar C-F bonds could form strong electric fields at the materials interfaces and affect the energy level alignment as suggested by the theoretical calculations [9] and recently shown experimentally by our group. [10][11][12] Collard et al [6,[13][14][15][16][17] reported pioneering works on the synthesis and the characterizations of poly(3-alkylthiophene)s (P3HTs) with various semifluroroalkyl substituents. They showed by Xray diffraction (XRD) that the alternating substitution of akyl and semifluoroalkyl chains induced the formation of bilayer lamellar structures in which the fluoroalkyl chains segregated from the alkyl layers.…”
mentioning
confidence: 99%